Histones in neutrophil extracellular traps (NETs) contain oxidative post-translational modifications induced by the myeloperoxidase oxidant hypochlorous acid - Helen Hemmling; Line A.E. Hallberg; Per Hägglund; Clare L. Hawkins (Redox Biology)
Extracellular traps (NETs) released by neutrophils during inflammation play a role in clearing infection but also contribute to disease pathology. NETs consist of a DNA backbone containing histones, anti-microbial granule proteins, such as myeloperoxidase (MPO), and other proteins. MPO remains enzymatically active and generates hypochlorous acid (HOCl) to kill pathogens. However, HOCl also readily reacts with proteins, but whether histones and other NET proteins are modified by this oxidant is unknown. This is significant as post-translational modification of histones alters their intracellular and extracellular reactivity. In this study, we used a proteomic approach to characterise the protein composition of NETs and identify HOCl-induced oxidative modifications on histones and other proteins. NETs were collected from primary neutrophils and the PLB-985 cell line and stimulated with phorbol myristate acetate (PMA) or nigericin, a bacterial peptide derived from Streptomyces hygroscopicus. There was evidence for Lys nitrile and aminoadipic semialdehyde formation, Tyr and Trp chlorination, and Met oxidation on histones and other proteins, including quinone oxidoreductase. Chlorination of Tyr-88 on histone H4 was particularly abundant and occurred to a greater extent in NETs from neutrophils exposed to PMA compared to nigericin, consistent with nigericin triggering NET release via a non-oxidative pathway. Chlorination of histone H4 Tyr-88 was also observed in the nuclear and cytoplasmic cell extracts of stimulated cells and could be decreased on treatment of the neutrophils with the MPO inhibitor AZD5904. These findings provide the first evidence that HOCl modifies proteins within NETs, particularly histone H4, which may be relevant in disease.